High-density high-thermal-conductivity silicon nitride ceramic as well as preparation method and application thereof

By optimizing the ceramic slurry formula and process steps, the problems of poor stability of photocured 3D printing ceramic slurry and low thermal conductivity of ceramic materials are solved, and the preparation and application of high-density high-thermal conductivity silicon nitride ceramics are realized, meeting the needs of complex shapes, high precision and high thermal conductivity applications.

CN119797935AActive Publication Date: 2025-04-11江淮前沿技术协同创新中心

Patent Information

Application Number
CN202510036102.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-09
Publication Date
2025-04-11
Estimated Expiration
2045-01-09

AI Technical Summary

Technical Problem

The existing photocuring 3D printed ceramic slurry has poor stability and the prepared ceramic materials have low thermal conductivity, making it difficult to meet the needs of complex shapes, high precision and high thermal conductivity applications.

Method used

By optimizing the slurry formula, including using a mixture of silicon nitride, magnesium oxide, and yttrium oxide as ceramic powder, and adding an appropriate amount of photosensitive resin, dispersant, initiator and defoaming agent, ball milling and photocuring molding, followed by vacuum discharging, air carbon removal and sintering, high-density high-thermal conduction silicon nitride ceramics are prepared.

Benefits of technology

It significantly improves the fluidity, dispersion and photocuring properties of silicon nitride ceramic slurry, ensures high precision and stability of the prints, and improves the thermal conductivity of ceramic materials. It is suitable for electronic devices, precision machinery and aerospace fields with high heat dissipation requirements.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119797935A_ABST
    Figure CN119797935A_ABST
Patent Text Reader

Abstract

The invention discloses high-density and high-thermal-conductivity silicon nitride ceramic as well as a preparation method and application thereof, and belongs to the technical field of ceramic material preparation. The preparation method comprises the following steps: 1, ball-milling and mixing: weighing 72-80% by mass of ceramic powder, 15-25% by mass of photosensitive resin, 2-5% by mass of a dispersant, 0.5-0.8% by mass of an initiator and 0.03-0.09% by mass of an antifoaming agent, and carrying out ball-milling and mixing to obtain a mixture; 2, carrying out photocuring molding; 3, carrying out vacuum glue removal; 4, carrying out air carbon removal; the light-cured silicon nitride ceramic slurry has the beneficial effects that the comprehensive performance of the light-cured silicon nitride ceramic slurry is remarkably improved by optimizing the types and the proportion of the slurry, the problems of poor flowability, sedimentation, reduction of heat conductivity and the like in the prior art are effectively solved, and a technical guarantee is provided for efficient and accurate manufacturing of high-performance silicon nitride ceramics. And the prepared silicon nitride ceramic piece has high thermal conductivity and is suitable for the fields of electronic devices and precision machinery with high heat dissipation requirements.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of ceramic material preparation, and in particular to a high-density and high-thermal-conductivity silicon nitride ceramic and a preparation method and application thereof. Background Art

[0002] Silicon nitride (Si3N4) has been widely used in electronics, aerospace, precision machinery and other fields due to its excellent mechanical properties, chemical stability and high thermal conductivity. In recent years, as the manufacturing industry has developed towards high performance and complex structures, traditional silicon nitride preparation methods (such as molding and injection molding) have been unable to meet the requirements of complex shapes, high precision and customization.

[0003] With its high-precision and high-efficiency molding characteristics, photocuring 3D printing technology provides a new solution for the manufacture of complex-shaped ceramic parts. However, traditional photocuring ceramic slurries are mostly oxide ceramics, and the research and development of nitride ceramic slurries still faces many challenges. In particular, high thermal conductivity silicon nitride slurry, due to the high viscosity, high solid content and optical properties of the material itself, its fluidity, dispersibility and curing properties in photocuring printing are difficult to take into account, which directly affects the accuracy and performance of the printed parts.

[0004] In the prior art, although some methods for improving the slurry formula have been proposed, such as improving the performance of silicon nitride slurry by introducing dispersants, modifying photoinitiators or optimizing slurry components, these methods often lead to a decrease in the thermal conductivity of the material while improving the slurry fluidity or curing speed, making it difficult to meet the needs of high thermal conductivity application scenarios. In addition, the stability of the slurry during long-term printing, such as sedimentation and uneven curing, has not been fully solved, resulting in large fluctuations in the quality of the printed parts.

[0005] The Chinese patent application document with publication number CN118420356A discloses a silicon nitride powder and a preparation method thereof, and silicon nitride ceramics. The preparation method of the silicon nitride powder comprises mixing liquid silicon halide and a silicon-based auxiliary agent with a particle size of 50nm-500nm in a protective atmosphere at a weight ratio of 100:1-11 to form a mixed slurry; introducing the mixed slurry into the interior of liquid ammonia in a reactor, and reacting the liquid silicon halide and the liquid ammonia in a temperature range of -50°C to 50°C to obtain a precursor powder; standing, filtering, separating and washing with a solvent to remove by-products to obtain a solid mixture; calcining the solid mixture in a nitrogen-containing atmosphere for 0.5-5h in a temperature range of 1300°C-1600°C to obtain silicon nitride powder; the weight ratio of liquid silicon halide to liquid ammonia is 1:3-15, and the silicon-based auxiliary agent is silicon powder or α-phase silicon nitride with an α-phase content greater than or equal to 93%. However, the thermal conductivity of silicon nitride ceramics prepared by this method is not high and needs to be further improved. Summary of the invention

[0006] The technical problem to be solved by the present invention is how to solve the problem of poor stability of existing photocurable 3D printing ceramic slurry and poor thermal conductivity of the prepared ceramic material.

[0007] The present invention solves the above technical problems through the following technical means:

[0008] The present invention provides a method for preparing a high-density and high-thermal-conductivity silicon nitride ceramic, comprising the following steps:

[0009] (1) ball milling and mixing: weighing 72-80% of ceramic powder, 15-25% of photosensitive resin, 2-5% of dispersant, 0.5-0.8% of initiator and 0.03-0.09% of defoamer by mass, and mixing by ball milling to obtain a mixture;

[0010] The ceramic powder is a mixture of silicon nitride, magnesium oxide and yttrium oxide in a mass ratio of 95:1.5:3.5;

[0011] (2) Stereolithography: The mixed material is sieved and introduced into the material tank of the light-curing printer. The prepared slice file is imported into the printer to start printing the green body;

[0012] (3) Vacuum debinding: placing the silicon nitride ceramic green body obtained in step (2) in a vacuum furnace for pre-firing;

[0013] (4) Air decarbonization: the material obtained in step (3) is placed in a muffle furnace for pre-burning;

[0014] (5) Sintering: The material obtained in step (4) is sintered to obtain high-density and high-thermal-conductivity silicon nitride ceramics.

[0015] Preferably, the average particle size of the silicon nitride, magnesium oxide and yttrium oxide is 0.1-1.0 μm.

[0016] Preferably, the photosensitive resin is a mixture of any one or more of HEA and HDDA.

[0017] Preferably, the dispersant is a mixture of any one or more of CPD03, CPD07, and CPD08.

[0018] Preferably, the initiator is a mixture of any one or more of CPI-01, CPI-02 and CPI-03.

[0019] Preferably, the defoaming agent is a mixture of any one or more of SN485, BYK-066N and TBP.

[0020] Preferably, in step (2), the mixture is sieved through a 300-mesh sieve.

[0021] Preferably, in step (3), the pre-calcination temperature is 380-420° C. and the pre-calcination time is 1-3 h.

[0022] Preferably, in step (4), the pre-calcination temperature is 550-650° C. and the pre-calcination time is 0.5-1.5 h.

[0023] Preferably, in step (5), the sintering temperature is 1800-2000° C. and the sintering time is 1-3 h.

[0024] The second aspect of the present invention provides a high-density and high-thermal-conductivity silicon nitride ceramic prepared by the above preparation method.

[0025] The third aspect of the present invention proposes the application of the above-mentioned high-density and high-thermal-conductivity silicon nitride ceramics in the fields of electronic instruments and precision machinery.

[0026] The beneficial effects of the present invention are:

[0027] 1. The present invention significantly improves the comprehensive performance of photocurable silicon nitride ceramic slurry by optimizing the type and ratio of slurry, effectively overcomes the problems of poor fluidity, sedimentation, and decreased thermal conductivity in the prior art, and provides technical guarantee for the efficient and precise manufacturing of high-performance silicon nitride ceramics. The prepared silicon nitride ceramic parts have high thermal conductivity and are suitable for electronic devices, precision machinery, and aerospace fields with high heat dissipation requirements.

[0028] 2. Excellent dispersibility and fluidity: By optimizing the type and amount of dispersant, the slurry of the present invention can still maintain good dispersibility under high solid content (40-60wt%) conditions, and the viscosity is controlled at 500-2000mPa·s (25°C), which effectively improves the fluidity and uniformity of the material during printing. There is no obvious sedimentation during long-term printing, ensuring stable quality of printed parts.

[0029] 3. Fast and uniform light curing performance: Adopting the adapted photoinitiator system and resin formula, the slurry cures quickly in the UV band (365-405nm), the curing time is less than 5 seconds, and the curing depth reaches 70-150μm, which meets the needs of precision 3D printing. The bonding force between the cured layers is strong, avoiding interlayer fracture or warping, and improving the overall mechanical properties of the printed parts.

[0030] 4. The produced ceramic parts have high thermal conductivity: The thermal conductivity of silicon nitride ceramic parts prepared after printing and sintering can reach more than 80W / m·K, which is equivalent to or even better than the performance of traditional silicon nitride ceramic parts. It is suitable for electronic devices with high heat dissipation requirements, precision machinery and aerospace fields. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 This is a graph showing the viscosity test results of the silicon nitride ceramic slurry prepared in Example 1 of the present invention;

[0032] Figure 2 This is a graph showing the viscosity test results of the silicon nitride ceramic slurry prepared in Comparative Example 1 of the present invention;

[0033] Figure 3 This is a graph showing the viscosity test results of the silicon nitride ceramic slurry prepared in Comparative Example 2 of the present invention; DETAILED DESCRIPTION

[0034] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0035] Unless otherwise specified, the test materials and reagents used in the following examples can be obtained from commercial sources.

[0036] If no specific techniques or conditions are specified in the examples, they can be carried out according to the techniques or conditions described in the literature in the art or according to the product instructions.

[0037] Experimental Example 1:

[0038] A method for preparing high-density and high-thermal-conductivity silicon nitride ceramics comprises the following steps:

[0039] Step 1: Ball milling and mixing: Weigh a certain amount of ceramic powder, photosensitive resin, dispersant, initiator and defoamer according to a solid content of 50 vol%. The ceramic powder is a mixture of silicon nitride, magnesium oxide and yttrium oxide in a mass ratio of 95:1.5:3.5 (the average particle size of silicon nitride, magnesium oxide and yttrium oxide is 0.6 μm), the photosensitive resin is HEA and HDDA (mass ratio 1:1), the dispersant is CPD07, the initiator is CPI-01, and the defoamer is SN-485. After conversion, the weighing ratio of each raw material in this process is:

[0040] Table 1

[0041]

[0042]

[0043] The raw materials were weighed and mixed in a planetary ball mill at 350 r / min for 4 h to obtain a mixed material.

[0044] Step 2: Photocuring: The slurry obtained in step 1 is introduced into the 382nm wavelength photocuring printer through a 300-mesh screen, and the exposure intensity is set to 100mW / cm 2, set the exposure time to 3s, set the scraper movement speed to 1000mm / min, import the prepared slice file into the printer and start printing the green body.

[0045] Step 3: Vacuum debinding: The silicon nitride ceramic green body obtained in step 2 is heated to 400° C. at 0.3° C. / min in a vacuum furnace and pre-fired for 2 hours to remove organic matter.

[0046] Step 4: Air decarbonization: The material obtained in step 3 is heated to 600°C at 10°C / min in a muffle furnace and pre-burned for 1 hour to remove the carbon residue of organic matter.

[0047] Step 5: Sintering: The material obtained in step 4 is heated to 1900° C. at 5° C. / min in air pressure and sintered for 2 hours to obtain a high-density and high-thermal-conductivity silicon nitride ceramic.

[0048] The slurry and the finished silicon nitride ceramic of Example 1 were tested for performance, and the test method was as follows:

[0049] The viscosity of the silicon nitride slurry was tested using a rotational viscometer model NDJ-8S, using a #4 rotor and setting the speed to 60RPM. The reading on the viscometer was read after the progress bar on the side of the viscometer reached the top.

[0050] Thermal conductivity of silicon nitride wafers was tested using the laser flash method.

[0051] The test results show that the viscosity of silicon nitride ceramic slurry is 2610mPa·s. Figure 1 (shown)

[0052] Three samples were randomly selected and tested for thermal conductivity. The results are shown in Table 2 below:

[0053] Table 2

[0054]

[0055] As can be seen from Table 1, the thermal conductivities obtained from the test are 80.670, 81.561, and 80.419 W / (m*K) respectively.

[0056] Embodiment 2:

[0057] The difference between this embodiment and embodiment 1 is that the average particle size of silicon nitride, magnesium oxide and yttrium oxide is 0.1 μm, and the rest is the same as embodiment 1.

[0058] Embodiment 3:

[0059] The difference between this embodiment and embodiment 1 is that the average particle size of silicon nitride, magnesium oxide and yttrium oxide is 1.0 μm, and the rest is the same as embodiment 1.

[0060] Embodiment 4:

[0061] The difference between this embodiment and embodiment 1 is: 72% ceramic powder, 25% photosensitive resin, 2.41% dispersant, 0.5% initiator and 0.09% defoaming agent, and the rest is the same as embodiment 1.

[0062] Embodiment 5:

[0063] The difference between this embodiment and embodiment 1 is that: 80% ceramic powder, 15% photosensitive resin, 4.17% dispersant, 0.8% initiator and 0.03% defoaming agent, and the rest is the same as embodiment 1.

[0064] Embodiment 6:

[0065] The difference between this embodiment and embodiment 1 is that: in step (3), the pre-firing temperature is 380°C and the time is 3 hours; in step (4), the pre-firing temperature is 650°C and the time is 0.5 hours; in step (5), the sintering temperature is 1800°C and the time is 3 hours, and the rest is the same as embodiment 1.

[0066] Embodiment 7:

[0067] The difference between this embodiment and embodiment 1 is that: in step (3), the pre-firing temperature is 420°C and the time is 1 hour; in step (4), the pre-firing temperature is 550°C and the time is 1.5 hours; in step (5), the sintering temperature is 2000°C and the time is 1 hour, and the rest is the same as embodiment 1.

[0068] Comparative Example 1:

[0069] The difference between this comparative example and Example 1 is that the powder ratio in step 1 is modified: the powder is a mixture of silicon nitride, magnesium oxide, and yttrium oxide in a mass ratio of 95:3.5:1.5. The rest is the same as Example 1. After conversion, the weighing ratio of each raw material in this process is:

[0070] Table 3

[0071]

[0072] The performance of the slurry and the finished silicon nitride ceramic of this comparative example 1 was tested using the same testing method as in Example 1.

[0073] The test results show that the viscosity of silicon nitride ceramic slurry is 2949mPa·s. Figure 2 (shown)

[0074] Three samples were randomly selected and tested for thermal conductivity. The results are shown in Table 4 below:

[0075] Table 4

[0076]

[0077] As can be seen from Table 4, the thermal conductivities obtained from the test are 45.289, 44.550, and 44.583 W / (m*K), respectively.

[0078] Comparative Example 2:

[0079] The difference between this comparative example and Example 1 is that the type of powder in step 1 is modified: the powder is only silicon nitride. The remaining steps are the same as Example 1. After conversion, the weighing ratio of each raw material in this process is:

[0080] Table 5

[0081]

[0082] The performance of the slurry and the finished silicon nitride ceramic of this comparative example 2 was tested using the same testing method as that of example 1.

[0083] The test results show that the viscosity of silicon nitride ceramic slurry is 2520mPa·s. Figure 3 (shown)

[0084] Three samples were randomly selected and tested for thermal conductivity. The results are shown in Table 6 below:

[0085] Table 6

[0086]

[0087] As can be seen from Table 6, the thermal conductivities obtained from the test are 22.254, 21.403, and 22.560 W / (m*K), respectively.

[0088] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing high-density and high-thermal-conductivity silicon nitride ceramics, characterized in that: The following steps are involved: (1) ball milling and mixing: weighing 72-80% of ceramic powder, 15-25% of photosensitive resin, 2-5% of dispersant, 0.5-0.8% of initiator and 0.03-0.09% of defoamer by mass, and mixing by ball milling to obtain a mixture; The ceramic powder is a mixture of silicon nitride, magnesium oxide and yttrium oxide in a mass ratio of 95:1.5:3.5; (2) Stereolithography: The mixed material is sieved and introduced into the material tank of the light-curing printer. The prepared slice file is imported into the printer to start printing the green body; (3) Vacuum debinding: placing the silicon nitride ceramic green body obtained in step (2) in a vacuum furnace for pre-firing; (4) Air decarbonization: the material obtained in step (3) is placed in a muffle furnace for pre-burning; (5) Sintering: The material obtained in step (4) is sintered to obtain high-density and high-thermal-conductivity silicon nitride ceramics.

2. The preparation method according to claim 1, characterized in that: The average particle size of the silicon nitride, magnesium oxide and yttrium oxide is 0.1-1.0 μm.

3. The preparation method according to claim 1, characterized in that: The photosensitive resin is a mixture of any one or more of HEA and HDDA.

4. The preparation method according to claim 1, characterized in that: The dispersant is a mixture of any one or more of CPD03, CPD07, and CPD08.

5. The preparation method according to claim 1, characterized in that: The initiator is a mixture of any one or more of CPI-01, CPI-02, and CPI-03; the defoamer is a mixture of any one or more of SN485, BYK-066N, and TBP.

6. The preparation method according to claim 1, characterized in that: In step (2), the mixture is sieved through a 300-mesh sieve.

7. The preparation method according to claim 1, characterized in that: In step (3), the pre-calcination temperature is 380-420°C and the time is 1-3 hours; in step (4), the pre-calcination temperature is 550-650°C and the time is 0.5-1.5 hours.

8. The preparation method according to claim 1, characterized in that: In step (5), the sintering temperature is 1800-2000° C. and the sintering time is 1-3 hours.

9. The high-density and high-thermal-conductivity silicon nitride ceramics prepared by the preparation method according to any one of claims 1 to 8.

10. Application of the high-density and high-thermal-conductivity silicon nitride ceramics according to claim 9 in the fields of electronic instruments and precision machinery.

Citation Information

Patent Citations

  • Silicon nitride powder, preparation method thereof and silicon nitride ceramic

    CN118420356A

  • Novel ceramic slurry as well as ceramic prepared by same and application thereof

    CN108658607A

  • Method for preparing high-strength and high-thermal-conductivity silicon nitride ceramic through two-step sintering

    CN113636844A

  • Method for preparing silicon nitride ceramic by sinking type DLP (Digital Light Processing) photocuring technology 3D (Three-Dimensional) printing

    CN114105650A

  • Silicon nitride ceramic 3D printing forming process

    CN118580084A

Cited By

  • Degreasing method of silicon nitride ceramic substrate

    CN121850684A